Promoting Citizenship Awareness Among Stateless Children: Advancing Global Goals for SDGs 1 and 5 - Makhroja, Mega Nisfa; Karjaya, Lalu Puttrawandi; Suhaimi, Nor Suzylan; Ajis, Mohd. Naem; Anjani, Gesta Tri; Putri, Diana Eka (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community project highlights the socio-legal challenges faced by Indonesian female workers in Malaysia, particularly those engaged in mixed status marriages with refugees or undocumented individuals such as the Rohingya. These women and their children often experience vulnerabilities due to the absence of legal recognition, which hinders their access to education, healthcare, and citizenship rights. Malaysia’s non-signatory position to the UN Refugee Convention, coupled with restrictive national laws, further complicates their situation, while Indonesia also lacks legal provisions to accommodate such cases. In response, this project seeks to raise citizenship awareness, emphasizing the risks of marrying non-state actors and the implications of statelessness. Implemented in collaboration with Universiti Sains Malaysia, Universiti Utara Malaysia, and the Rohingya Learning Center, the initiative combines socialization, training, and mentorship to empower women with essential knowledge. By integrating social media campaigns and academic outputs, the program aims to promote the Sustainable Development Goals (SDGs) 1 (No Poverty) and 5 (Gender Equality), while also advocating for policy reforms. Through this approach, the project aspires to reduce vulnerabilities, strengthen community resilience, and contribute to broader discussions on migration and refugee rights in Malaysia.